Project-Based Learning (PjBL) in Electronics Course : An Arduino-Based Automatic Watering Prototype - Yeyen, Yustina Yesisanita; Yunita, Maria (Journal of Innovative Science Education, 2025)
The Electronics course necessitates the integration of theoretical knowledge, practical skills, and scientific communication competencies. Technology-based Project-Based Learning (PjBL) provides an effective means to address these requirements by engaging students in meaningful, hands-on projects. This study examines the implementation of Arduino-based PjBL through the development of an automatic watering prototype and evaluates its impact on students’ scientific communication skills in the Electronics course. A qualitative research design was adopted, with participants comprising students enrolled in the course. Data collection methods included classroom observations, project documentation, and student reflections. Scientific communication skills were assessed using six indicators: clarity of delivery, appropriate use of scientific terminology, structure and logic of presentation, data interpretation, responses to questions, and written communication. The results demonstrated that students presented their projects more systematically, beginning with problem identification, followed by system design, testing results, and conclusions. Students were able to explain circuit errors and propose corrective actions logically. Additionally, written reports became more structured and were substantiated by measurement data. Overall, the findings suggest that Arduino-based PjBL effectively supports the development of students’ scientific communication skills in Electronics education.